Neuropathology of Pediatric SARS-CoV-2 Infection in the Forensic Setting: Novel Application of Ex Vivo Imaging in Analysis of Brain Microvasculature - Stram, Michelle N.; Seifert, Alan C.; Cortes, Etty; Akyatan, Alara; Woodoff-Leith, Emma; Borukhov, Valeriy; Tetlow, Amber; Alyemni, Dimath; Greenberg, Michael; Gupta, Avneesh; Krausert, Amanda; Mecca, Lauren; et al. (Frontiers in Neurology, 2022)
Two years into the COVID-19 pandemic, there are few published accounts of postmortem SARS-CoV-2 pathology in children. We report 8 such cases (4 infants aged 7-36 weeks, 4 children aged 5-15 years). Four underwent ex vivo magnetic resonance neuroimaging, to assist in identification of subtle lesions related to vascular compromise. All infants were found unresponsive (3 in unsafe sleeping conditions); all but 1 had recent rhinitis and/or influenza-like illness (ILI) in the family; 1 had history of sickle cell disease. Ex vivo neuroimaging in 1 case revealed white matter (WM) signal hyperintensity and diffuse exaggeration of perivascular spaces, corresponding microscopically to WM mineralization. Neurohistology in the remaining 3 infants variably encompassed WM gliosis and mineralization; brainstem gliosis; perivascular vacuolization; perivascular lymphocytes and brainstem microglia. One had ectopic hippocampal neurons (with pathogenic variant in DEPDC5). Among the children, 3 had underlying conditions (e.g., obesity, metabolic disease, autism) and all presented with ILI. Three had laboratory testing suggesting multisystem inflammatory syndrome (MIS-C). Two were hospitalized for critical care including mechanical ventilation and extracorporeal membrane oxygenation (ECMO); one (co-infected with adenovirus) developed right carotid stroke ipsilateral to the ECMO cannula and the other required surgery for an ingested foreign body. Autopsy findings included: acute lung injury in 3 (1 with microthrombi); and one each with diabetic ketoacidosis and cardiac hypertrophy; coronary and cerebral arteritis and aortitis, resembling Kawasaki disease; and neuronal storage and enlarged fatty liver. All 4 children had subtle meningoencephalitis, focally involving the brainstem. On ex vivo neuroimaging, 1 had focal pontine susceptibility with corresponding perivascular inflammation/expanded perivascular spaces on histopathology. Results suggest SARS-CoV-2 in infants may present as sudden unexpected infant death, while in older children, signs and symptoms point to severe disease. Underlying conditions may predispose to fatal outcomes. As in adults, the neuropathologic changes may be subtle, with vascular changes such as perivascular vacuolization and gliosis alongside sparse perivascular lymphocytes. Detection of subtle vascular pathology is enhanced by ex vivo neuroimaging. Additional analysis of the peripheral/autonomic nervous system and investigation of co-infection in children with COVID-19 is necessary to understand risk for cardiovascular collapse/sudden death.